Military and militarism: interdisciplinary perspectives on the military universe - Robba, Olívia da Rocha (2020)
It is with great satisfaction and joy that we present to the readers of Temáticas the dossier "Militaries and militarisms: interdisciplinary perspectives on the military universe." Composed of 11 articles that analyze the Armed Forces, their activities, thinking and capillarity in relation to society, this dossier is an attempt to shed light on themes and problems that involve the military universe. With the intention of contributing to a better understanding of this universe, the authors gathered here brought discussions that address and broaden the view on the barracks, either with old themes about new perspectives or with new themes that started to call the attention of historians, anthropologists, scientists researchers and researchers who are interested in issues involving the military.